Prospective Volumetric Assessment of the Liver on a Personal Computer by Nonradiologists Prior to Partial Hepatectomy - Dello, Simon A. W. G. (Springer-Verlag, 2010)
BACKGROUND: A small remnant liver volume is an important risk factor for posthepatectomy liver failure. ImageJ and OsiriX(®) are both free, open-source image processing software packages. The aim of the present study was to compare ImageJ and OsiriX(®) in performing prospective computed tomography (CT) volumetric analysis of the liver on a personal computer (PC) in patients undergoing major liver resection. METHODS: Patients scheduled for a right hemihepatectomy were eligible for inclusion. Two surgeons and one surgical trainee measured volumes of total liver, tumor, and future resection specimen prospectively with ImageJ and OsiriX(®). A radiologist also measured these volumes with CT scanner-linked Aquarius iNtuition(®) software. Resection volumes were compared with the actual weights of the liver specimens removed during surgery, and differences between the measured liver volumes were analyzed. RESULTS: A total of 15 patients (8 men, 7 women) with a median age of 63 years (48–79 years) were included. There was a significant correlation between the measured weights of resection specimens and the volumes calculated prospectively with ImageJ and OsiriX(®) (r = 0.89; r = 0.83, respectively). There was also a significant correlation between the volumes measured with radiological software iNtuition(®) and the volumes measured with ImageJ and OsiriX(®) (r = 0.93; r = 0.95, respectively). CONCLUSIONS: There were no major differences in total liver volumes, resection volumes, or tumour volumes for these three software packages. Prospective hepatic CT volumetry with ImageJ or OsiriX(®) is reliable and can be accurately used on a PC by nonradiologists. ImageJ and OsiriX(®) yield results comparable to the radiological software iNtuition(®).